OPTIMIZING BUDGET ALLOCATION FOR SUPPORTING EDUCATIONAL FACILITIES IN ISLAMIC BOARDING SCHOOLS - Muhammad Ali Gunawan; Sabilal Rosyad; Hawa Husna Ab Ghani (Istifkar: Media Transformasi Pendidikan, 2025)
Optimizing budget allocation for educational facilities in Islamic boarding schools is essential to ensure sustainable education quality. This study aims to optimize budget allocation to support educational facilities at Al-Qutub Islamic Boarding School, Wonopringgo, Pekalongan Regency, using a Bayesian Decision Making approach with the Markov Chain Monte Carlo (MCMC) method. Data were collected through questionnaires, observations, and interviews to gather insights on facility conditions, current budget allocation, and additional facility needs. Data analysis employed the MCMC method, enabling decision-making based on the probabilistic distribution of the collected data. The findings indicate that budget allocation optimized through the Bayesian model results in a more effective distribution, addressing urgent facility priorities that directly enhance educational quality. This study contributes a budget analysis model applicable to Islamic educational institutions in Indonesia. Theoretically, it enriches the literature on educational budget management in Islamic boarding schools using Bayesian statistical approaches, while practically, it assists school administrators in allocating budgets more efficiently and accurately in line with educational needs.